An experimental study of fog and cloud computing in CEP-based Real-Time IoT applications - Mondragón-Ruiz G. (2021)
This work has been partially funded by the Spanish Ministry of Science, Innovation and Universities (ref. RTI2018-098156-B-C52), by the Research Plan of the University of Castilla-La Mancha (ref. 2019-GRIN-27060), and by FONDECYT / World Bank (ref. 026-2019 FONDECYT-BM-INC.INV).